Clinical and economic impact of compression in the acute phase of deep vein thrombosis. (13th July 2018) - Amin, E. E.; Joore, M. A.; ten Cate, H.; Meijer, K.; Tick, L. W.; Middeldorp, S.; Mostard, G. J. M.; ten Wolde, M.; van den Heiligenberg, S. M.; van Wissen, S.; van de Poel, M. H. W.; Villalta, S.; et al.
Abstract : Essentials The value of compression therapy in acute phase of deep vein thrombosis is still unclear. Patients with deep vein thrombosis received acute compression hosiery, bandaging, or none. Acute compression reduces irreversible skin signs related to post thrombotic syndrome. Compression hosiery may be the preferred choice for the acute phase Summary: Background: The effectiveness of compression therapy in the acute phase of deep vein thrombosis (DVT) is not yet determined. Objectives: To investigate the impact of compression therapy in the acute phase of DVT on determinants of the Villalta score, health‐related quality of life (HRQOL), and costs. Patients/Methods: Eight hundred and sixty‐five patients with proximal DVT (substudy of the IDEAL DVT study) received, immediately after DVT diagnosis, either no compression, multilayer bandaging, or hosiery. In the acute phase and 3 months after diagnosis, HRQOL was determined by use of the EQ‐5D, SF6D, and VEINES‐QoL intrinsic method (VEINES‐QoL int ). At 3 months, signs and symptoms were assessed for the total and separate items of the Villalta score, and healthcare costs were calculated. Results: The compression groups had lower overall objective Villalta scores than the no‐compression group (1.47 [standard deviation (SD) 1.570] and 1.59 [SD 1.64] versus 2.21 [SD 2.15]). The differences were mainly attributable to irreversible skin signs (induration, hyperpigmentation, and venectasia) and pain on calf compression. Subjective and total Villalta scores were similar across groups. Differences in HRQOL were only observed at 1 month; HRQOL was better for hosiery (EQ‐5D 0.86 [SD 0.18]; VEINES‐QoL int 0.66 [SD 0.18]) than for multilayer compression bandaging (EQ‐5D 0.81 [SD 0.23; VEINES‐QoL int 0.62 [SD 0.19]). Mean healthcare costs per patient were €417.08 (€354.10 to €489.30) for bandaging, €114.25 (€92.50 to €198.43) for hosiery, and €105.86 (€34.63 to €199.30) for no compression. Conclusions: Initial compression reduces irreversible skin signs, edema, and pain on calf compression. Multilayer bandaging is slightly more effective than hosiery, but has substantially higher costs, without a gain in HRQOL. From a patient and economic perspective, compression hosiery would be preferred when initial compression is applied. Trial registration: IDEAL DVT study ClinicalTrials.gov number, NCT01429714.